THE INFLUENCE OF BRAND, TASTE, AND PACKAGING ON CONSUMER LOYALTY TOWARD LE MINERALE PRODUCTS (A CASE STUDY OF STUDENTS AT THE FACULTY OF ECONOMICS, SIMALUNGUN UNIVERSITY) - Liharman Saragih; Afrizal Habib Rojali; Heppy Clara Juwita Sinaga; Natanael Agustin Girsang; Fachriza D. Akmal; Nizwan Noufal Ariffuddin (Jurnal Review Pendidikan dan Pengajaran, 2026)
This study aims to analyze the influence of brand, taste, and packaging on consumer loyalty toward Le Minerale bottled drinking water, with a case study on students of the Faculty of Economics, Simalungun University in the 2025/2026 academic year. The research method used is quantitative with a survey approach. The research population consisted of all active students of the Faculty of Economics, Simalungun University who had consumed Le Minerale, with a sample of 96 respondents selected using a purposive sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis used multiple linear regression with the help of SPSS version 26 software. Results show that brand has a positive and significant effect on consumer loyalty (t = 4,217; p < 0,05), taste has a positive and significant effect on consumer loyalty (t = 3,854; p < 0,05), and packaging has a positive and significant effect on consumer loyalty (t = 3,129; p < 0,05). Simultaneously, all three variables significantly influence consumer loyalty (F = 38,742; p < 0,05) with a coefficient of determination (R²) of 0,556, meaning 55,6% of consumer loyalty variation can be explained by these three variables. These findings imply that companies need to maintain and strengthen brand equity, taste consistency, and packaging innovation to retain consumer loyalty, particularly among students.